Education and training for records management in the electronic environment - the (re)search for an appropriate model. Professional development, Training, Education, Models, Records management - McLeod J.; Hare C.; Johare R. (Information Research: An International Electronic Journal)
Managing records in the e-environment constitutes a complex and challenging strategic issue for all organizations because IT systems shape business operations and the nature and management of the records they generate. IT personnel, administrators, archivists, records creators and users, as well as records managers, must work in partnership to ensure the authenticity, reliability, integrity, and ongoing usability of records. Education and training provision must evolve to fulfil the needs of all of these players in this complex environment. Everyone needs a macro-level understanding, combined with micro-level knowledge and practical skills, determined by their role, responsibility and level of systems interface. This matrix of horizontal and vertical mappings defines a pathway tailored to the individual's recordkeeping role. The requirement is holistic not atomistic, because it is integrated with the business processes. This study critically evaluates existing initiatives and initial results of a doctoral study searching for a best practice model.